Data structures - Gilberg, Richard F. (Brooks/Cole, 2001)
This new text makes it simple for beginning computer science students to design algorithms first using pseudocode and then build them using the C++ programming language. Based on Gilberg and Forouzan's successful text, Data Structures: A Pseudocode Approach with C, this new book emphasizes a practical approach to data structures